Computational simulation of a non-destructive testing technique for steel bar sizing in concrete structures using eddy current testing and neural networks - De Alcantara, N. P. [UNESP] (2010)
This paper proposes a new type of non-destructive testing (NDT) for reinforced concrete structures, in order to identify the components of their reinforcement. In the proposed methodology a time varying electromagnetic field is generated close to the structure by electromagnetic devices specially designed for this purpose. The presence of ferromagnetic materials (the steel bars of the reinforcement) immersed in the concrete disturbs the magnetic field at the surface of the structure. These field alterations can be detected by sensors coils placed on the concrete surface. Variations in the bar position, cross section of the bar and number of bars in the structure originate slightly different values for the induced voltages at the coils. In this paper, a finite element program was used to simulate the behavior of the electromagnetic field and artificial neural networks were used to perform the identification of the bars. © Civil-Comp Press, 2010.